Subject of Rape. - Chau, Monica; Feldman, Hannah J.L.; Kabat, Jennifer; Kruse, Hannah (New York : Whitney Museum of American Art, 1993)
Bacher, Lutz ; Chenoweth, Kathy ; Diggs, Peggy ; Fields, Laura ; King, Ashley ; Lacy, Suzanne ; Mendieta, Ana ; Montgomery, Jennifer ; Murray, Maryanne ; Orloff, Deborah ; Ragusa, Kym ; Rivera Castro, Eva ; Rothfarb, Shari ; Sandrow, Hope ; Schorr, Collier ; Simpson, Lorna ; Sligh, Clarissa ; Soo Jim Kim ; Spero, Nancy ; Strosser, Margie ; Tewes, Robin ; West, Annie ; Williams, Sue ; Wojnarowicz, David
bibliog. p. 88-89
Engels
The Subject of Rape, Whitney Museum of American Art, New York, June 23 - August 1993
boek